Integration of Islamic real estate investment trusts in Malaysia: is it an issue for investors? - Mohd Yahya Mohd Hussin,; Noor Hashimah Husaini,; Fidlizan Muhammad,; Azila Abdul Razak,; Fatimah Salwa Abdul Hadi, (School of Social, Development and Environmental Studies, Faculty of Social Science and Humanities, Universiti Kebangsaan Malaysia, 2016)
Various stakeholders and academicians have shown their interest in the study of capital market instruments such as stock market, bond and real estate investment trust (REITs). As such, there rises a need to review the importance of capital markets integration. This study took a closer look at the co-integration between Islamic real estate investment trust counters in Malaysia by applying the Vector Auto Regression (VAR) method. Data were generated by processing monthly data from January 2007 to December 2013 obtained from authorized sources. The findings indicated that there was no long-run or equilibrium relationship between the Islamic al-Aqar, al-Hadharah and Axis counters. Based on the results, it can be concluded that the Islamic REIT companies in Malaysia do not integrate each other in the long run. This will create opportunity for investors to diversify their investment portfolios in Malaysia. As seen from the Granger causality view, the Hadharah and Axis returns were driven by al-Aqar returns in the short run.